Analysis of Perceptions and Preferences of Electric Car Users: A Qualitative Study using Nvivo 14 - Ditra Krahara, Yuwan; Harwani, Yuli; Astini, Rina; Prayoga Kasmo, Arief Bowo (Jurnal Locus Penelitian dan Pengabdian, 2026)
The transition to electric vehicles (EVs) represents a critical pathway toward sustainable transportation and carbon emission reduction globally. However, in developing countries like Indonesia, EV adoption rates remain significantly low despite increasing environmental awareness and government incentive programs. This study aims to analyze the perceptions and preferences of electric car users in Indonesia through a qualitative approach based on NVivo 14. Involving 15 informants from the Banten region, this study explored motivations, obstacles, and psychological and structural factors that influence consumers' decisions to adopt electric vehicles. The results show that although awareness of environmental benefits is relatively high, purchasing decisions are more influenced by cost efficiency and long-term savings. The findings also reveal the existence of an awareness–action gap, where awareness is not always followed by action. Two other important issues that emerged were charging anxiety due to limited charging infrastructure and low government policy trust due to uncertainty regarding government incentives. These three constructs are not covered by the five classical dimensions of the Diffusion of Innovation (DOI) theory, so this study offers an expansion of the DOI framework to make it more contextual to Indonesia's social, economic, and policy conditions. As a result, the proposed new conceptual model not only explains the purchase intent factor more comprehensively but can also serve as a reference in the formulation of policy strategies and intervention designs that encourage the sustainable adoption of electric vehicles.